The Effectiveness Analysis of Village Funds Management Planning - Yuliana Yuliana; Cut Rahmawati; Yulfrita Adamy; Edwar Edwar; Azlim Azlim (Proceedings of AICS - Social Sciences, 2018)
The effectiveness analysis illustrates the local authority ability to realize Village Finance or Village Budget Allocation to implement planned programs compared to established targets based on potential real value. The management of village funds in Aceh seems to be ineffective where there is an unaccountable village financial realization as well as the planned program is inconsistent with the initial target. Therefore, it is necessary to find the effectiveness of the use of village funds. This study takes a case study in Lambaya, Simeulue Tengah Subdistrict of Simeulue District in 2015-2016. This study aims at determining the level of effectiveness of village funds management planning in village development. Data collection methods were conducted qualitatively through observation, interview, documentation and questionnaire. Data analysis techniques used descriptive qualitative method. The analysis used to calculate the effectiveness level of Village Finance or Village Funds Allocation in Lambaya from 2015-2016 uses the effectiveness ratio’s formula. In which the effectiveness of an organization is said to be good if the ratio achieved at least 90% to 100%. The results show that the effectiveness of village funds management from 2015-2016 has been in the very effective category that is in 2015 of 100.96% and in 2016 of 100.21%. At the planning stage is seen ineffective level, as society participation is still low. At the stage of implementation has reached an effective level where the budget can be used properly. At the village funds accountability stage has been effective, where direct preparation is conducted by the Lambaya’s local authority and evaluate with community leaders and the Village Council Board openly. Thus in the management of village funds need to be considered at the planning stage. All aspects of society need to be actively involved to generate effective use of village funds. Also, it is necessary to improve the quality of human resources (HR).Keywords: effectiveness of financial planning, development, village funds.